The Effect of Inquiry-Based Learning on Pharmacist Students - Rizki, Muhammad Ikhwan; Lingga, Herningtyas Nautika; Intannia, Difa; Rahmatullah, Satrio Wibowo; Putra, Aditya Maulana Perdana; Silviana, Mega (Vidya Karya, 2024)
One of the influential factors in shaping professional health workers is the learning process during education. The professional attitude of pharmacy students can be modified with innovative learning methods. Inquiry-Based Learning (IBL) emphasizes students' involvement in systematically, critically, and logically gathering information so that they can formulate their findings. This study aims to determine the effect of IBL on pharmacist professional study program education students taking Pharmacy Communication and Health Promotion courses. This study employed quasi-experimental research with a group Pretest-Posttest Design. The study subjects were 40 students of the Pharmacist Professional Education Study Program. The students got learning interventions with IBL method. IBL stages consist of IBL orientation, problem formulation, hypothesis formulation, data collection, hypothesis testing, conclusion formulation, and learning evaluation. Assessment instrumentation included pretests, posttests, reports, and student satisfaction questionnaires. Pretest and posttest data were statistically analyzed with SPSS. The implementation of IBL resulted in an increase in mean scores from 59.82 on the pretest to 92.83 on the posttest. There is a statistically significant difference between these results (Asymp. Sig 0.000). The proportion of student reports rated as excellent 70%, good 20%, and sufficient 5%. Student satisfaction with the learning method reached an average of 93.94%. Inquiry-based learning increases the knowledge of Pharmacist Professional Education Study Program students in the Pharmacy Communication and Health Promotion courses.